MAHASIVARATRI AS INTEGRAL HINDU SPIRITUALITY: ONTOLOGICAL, EPISTEMOLOGICAL, AND AXIOLOGICAL PERSPECTIVES - I Gede Sudha Cahyana; I Wayan Putra Adi Subawa (INTERNATIONAL JOURNAL ON HINDU CULTURE, 2026)
This article examines Mahasivaratri as an integrated form of Hindu spirituality through ontological, epistemological, and axiological perspectives. Ontologically, Mahasivaratri is interpreted as a sacred symbol of the union between human consciousness and the Absolute Reality, where Śiva represents the cosmic principle that transcends and permeates the universe. Epistemologically, the observance demonstrates a holistic model of spiritual knowledge derived from scriptural authority, ritual symbolism, ascetic practice, and contemplative experience, indicating that religious praxis functions as a transformative method of knowing. Axiologically, the celebration embodies ethical, spiritual, and ecological values, including self-discipline, compassion, mental purification, and harmony with nature. The study employs qualitative textual analysis of Hindu scriptures, classical literature, and traditional commentaries, including Nusantara sources, to interpret symbolic and theological meanings. The findings reveal that Mahasivaratri is not merely an annual ritual but a comprehensive spiritual system designed to facilitate inner transformation, moral refinement, and cosmic awareness. The concept of anugraha (divine grace) emerges as a central theological principle that links metaphysical truth with existential experience, emphasizing that spiritual liberation arises through inner purification and disciplined practice. Therefore, Mahasivaratri can be understood as a paradigm of integral Hindu spirituality that unites metaphysics, knowledge, and ethical life within a single transformative religious framework.